Preparation of PbF2:Ho3+, Er3+, Yb3+ phosphors and its multi-wavelength sensitive upconversion luminescence mechanism. (November 2018) - Wu, Tingting; Li, Biao; Sun, Jialiang; Shao, Mengting; Ma, Xiaoyi; Bai, Zhaohui
Graphical abstract: The UC luminescence propertiesand mechanism are analyzed under excitation of 1064 nm and 1550 nm for the first time. The UC luminescence mechanism of the samples excited by 1064 nm laser is shown in Fig. 1(a) and (b). The results show that the intense green emission at 541 nm and 548 nm originates from the 4 F9/2 → 4 I15/2 transition of Ho 3+ ions and the 4 S3/2 → 4 I15/2 transition of Er 3+ ions. The weak green emission at 523 nm derives from the 2 H11/2 → 4 I15/2 transition of Er 3+ ions and the weak red emission at 653 nm and 667 nm originates from the 5 F5 → 5 I8 transition of Ho 3+ ions and the 4 F9/2 → 4 I15/2 transition of Er 3+ ions. The UC luminescence mechanism of the samples excited by 1064 nm laser is shown in Fig. 1(c) and (d). The results present that the green emission at 546 nm derives from the 5 F4 ( 5 S2 )→ 5 I8 transition of Ho 3+ ions and the 4 S3/2 → 4 I15/2 transition of Er 3+ ions. On the other hand, the weak red emission at 653 nm and 667 nm derives from the 5 F5 → 5 I8 transition of Ho 3+ ions and the 4 F9/2 → 4 I15/2 transition of Er 3+ ions. (a) Energy level diagram for Ho 3+, Er 3+ and Yb 3+ ions excited by 1064 nm. (b) Scheme of cross-relaxation between Ho 3+ and Er 3+ ions. (c) Energy level diagram for Ho 3+, Er 3+ and Yb 3+ ions excited by 1550 nm. (d) Scheme of cross-relaxation between Ho 3+ and Er 3+ ions. Highlights: In this paper, PbF2 : Ho 3+, Er 3+, Yb 3+ phosphors are prepared by a high-temperature solid-state method for the first time. The crystal structure of the as-prepared phosphors is refined. The upconversion luminescence properties and mechanism of the as-prepared phosphors are analyzed under excitation of 1064 nm, 1550 nm for the first time. Abstract: In this paper, PbF2 : Ho 3+, Er 3+, Yb 3+ phosphors are prepared by a high-temperature solid-state method. The crystal structure acquired by X ray powder diffractometer shows that the resultant phosphor is a pure cubic PbF2 crystal. The upconversion (UC) emission spectra of samples are performed by a fluorescence spectrophotometer coupled with lasers of 980 nm, 1064 nm and 1550 nm, presenting the green emission in the range of 541∼548 nm and red emission in the range of 653–667 nm, corresponding to the excitation path: Ho 3+ : 4 F9/2 → 4 I15/2, Er 3+ : 4 S3/2 → 4 I15/2, Er 3+ : 4 F9/2 → 4 I15/2 and Ho 3+ : 5 F5 → 5 I8 . Finally, the UC luminescence mechanism is analyzed under excitation of different wavelengths. The result shows that the phosphors have a promising prospect for application in anti-counterfeiting technologies and solar cell field.